2003
DOI: 10.1074/jbc.m211958200
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Potentiates Transforming Growth Factor β (TGFβ)-induced Apoptosis and Expression of the BH3-only Protein Bim in WEHI 231 B Lymphocytes

Abstract: Transforming growth factor-␤ (TGF␤) is a potent growth inhibitor and inducer of apoptosis in B lympho

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 63 publications
7
96
0
Order By: Relevance
“…At the same time, there was an increase in levels of death-associated protein kinase, which is a target of transcriptional activation by Smad. 16 In accordance with reports that Bim is activated and functions as an important initiator of TGF-β-induced apoptosis in both a human gastric carcinoma cell line 26 and a B-cell line, 28 Bim was upregulated in CLL cells cultured with FK506. Bmf is another BH3-only protein implicated in TGF-β-induced apoptosis 27 which plays a role in regulating the growth and survival of B cells 28 and CLL cells.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…At the same time, there was an increase in levels of death-associated protein kinase, which is a target of transcriptional activation by Smad. 16 In accordance with reports that Bim is activated and functions as an important initiator of TGF-β-induced apoptosis in both a human gastric carcinoma cell line 26 and a B-cell line, 28 Bim was upregulated in CLL cells cultured with FK506. Bmf is another BH3-only protein implicated in TGF-β-induced apoptosis 27 which plays a role in regulating the growth and survival of B cells 28 and CLL cells.…”
Section: Discussionsupporting
confidence: 73%
“…We also evaluated the expression levels of the anti-apoptotic Bcl-2 and Bcl-xL, and the pro-apoptotic BH3-only molecules, Bim and Bmf, which are implicated in commitment to TGF-β-induced apoptosis. [26][27][28] We found that the appearance of death-associated protein kinase was accompanied by a decrease of Bcl-2 and Bcl-xL and an increase of Bim ( Figure 5A). Bim is an essential regulator of lymphoid system homeostasis and appears to be essential for induction of Bcell apoptosis.…”
Section: Fk506 Modulates the Expression Levels Of Both Pro-and Anti-amentioning
confidence: 93%
See 1 more Smart Citation
“…4E). Finally, we tested the expression of several TGF-␤ target genes, including Smad7, c-Myc, and Bim (32)(33)(34)(35)(36). As shown in Fig.…”
Section: Pak2 Phosphorylates Smad2 At Ser 417 and The Phosphorylationmentioning
confidence: 99%
“…Other proteins that play a facilitative role in TGFb-induced death, but whose expression is not induced by it, include the adaptor proteins DAXX (Perlman et al, 2001) and CD2AP (Schiffer et al, 2004) and the septin ARTS- (Larisch et al, 2000). In addition, the proapoptotic Bcl-2 family protein Bim is a Smad3-dependent TGFb-induced protein in B lymphocytes (Wildey et al, 2003), whose binding to Bcl-X L increases during TGFb-induced apoptosis (Ohgushi et al, 2005). Furthermore, Bad and Bid (Kim et al, 2004) undergo caspase-dependent cleavage to more potently apoptotic forms after TGFb stimulation, while the antiapoptotic proteins Bcl-X L and Bcl-2 have been demonstrated to undergo TGFb-mediated downregulation in several cell types (Saltzman et al, 1998;Francis et al, 2000;Chipuk et al, 2001;Kanamaru et al, 2002).…”
Section: Introductionmentioning
confidence: 99%